Interpresentasi Estetika Fetishisme Terhadap Hewan Yang Sudah Mati Dalam Seni Patung - Iqbal, Mochammad; Ruta, I Made; Mudana, I Wayan (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2022)
Commodity dimensions in art include exchange value, commercial value, valorization, commodity fetishism, market logic. Reading art through the commodity dimension is an attempt to reveal the economic value contained in the work of art. This value is not only contained in works of art, but also has a deterministic power to build and organize art. art that is part of a commodity—resulting in an aesthetic category, called “commodity aesthetics”. This is the kind of aesthetic, which builds attraction through the workings of the "immediate effect" and provokes an immediate reaction, such as cuteness, fascination or eroticism. Art and science actually have the same things are mutually sustainable, cannot be separated. From the selection of materials, to manufacturing techniques, to the curation stage, it's all a collaboration of art and science. Leonardo da Vinci's realist works are also a merger of fine art and human anatomy—biology. It is from da Vinci's works that the author is compelled to create creation that are related to the biological sciences. It is also an innovation, although not the first in the world, in the arts in Indonesia, with the hope of breaking the arts that always maintain the quo status